A bright spark is not necessarily a wise person. Old Testament and contemporary perspectives on wisdom and intelligence - Heerden, Schalk Willem van (Old Testament essays, 1996)
The aim of this article is to investigate the problems encountered when endeavouring to define such a multifaceted phenomenon as wisdom. Special attention is given to R.N. Whybray's definition of wisdom as a human attribute. He defined it as 'superior intelligence/intellectual ability in a general sense.' Whybray's definition prompted this investigation of the relationship between wisdom and intelligence or knowledge. In it the so-called 'wisdom compass', provided by the Egyptologist Aleida Assmann, is implemented.